PENGARUH PRODUKTIVITAS TENAGA KERJA TERHADAP PEKERJAAN PLESTERAN (Studi Kasus : Proyek Pembangunan Masjid Babbusalam Sabil Barakah) - Atmiko, Kgs. M. Widi; Umari, Zuul Fitriana; Asmawi, Bazar; Septriansyah, Verinazul (LATERAL: Jurnal Teknik Sipil, 2024)
A project is a temporary activity that has clear goals and objectives, lasts for a limited period of time, with a certain cost allocation. This research was conducted to find out how much labor productivity there is in plastering work on the Babbusalam Sabil Barakah Mosque construction project and what factors influence the productivity of plastering work on the Babbusalam Sabil Barakah Mosque construction project. The research was conducted by observing the productivity level of 32 workers and accompanied by filling out a questionnaire. Productivity observations used the work sampling method by calculating worker utility factors which were carried out for 3 days for each worker. The average value of the worker productivity utility factor in plastering work on the Babbusalam Sabil Barakah Mosque construction project is 89.57%. The variables that have been determined have a significance of 0.000<0.005 (the required sig) so that they simultaneously have an influence on the level of productivity. Partially, 9 factors that influence the productivity variable have a calculated T value for each variable that exceeds the T table value of 2.074.